VD_FINDINFO Jug-par-déf / 2023 / 1 vom 10. November 2023 - VD Tribunal cantonal (2023)
MARQUE DE HAUTE RENOMMÉE, PROTECTION DES MARQUES | 109 al. 1 LDIP, 109 al. 2 LDIP, 110 al. 1 LDIP, 3 al. 2 let. a LPM, 124 al. 2 CPC (CH), 147 al. 3 CPC (CH), 153 al. 2 CPC (CH), 153 CPC (CH), 223 al. 1 CPC (CH), 223 al. 2 CPC (CH)